Daño Psicológico en NNA víctimas Indirectas del feminicidio en Colombia, Argentina, Ecuador y España - Vargas Hernández, Angee Joanna (Universidad Antonio Nariño, 2022)
The present work aims to describe, based on a systematic review of the literature in countries such as Colombia, Argentina, Ecuador and Spain, the most relevant findings regarding psychological damage in children and adolescents who have been exposed as indirect victims of femicide, categorizing the contents found in the documents, providing information that helps in the evaluation of the psychological damage in this population